2000
DOI: 10.1084/jem.191.12.2031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-XL Restores Cell Survival, but Not Proliferation and Effector Differentiation, in Cd28-Deficient T Lymphocytes

Abstract: Lymphocytes deficient in the T cell costimulatory molecule CD28 exhibit defects in cell survival, clonal expansion, and differentiation into effector cells. It is known that CD28-mediated signaling results in the upregulation of the Bcl family member Bcl-XL. To investigate the role that Bcl-XL plays in the various functions of CD28, we expressed Bcl-XL in CD28-deficient primary T lymphocytes using retrovirus-mediated gene transfer. T cells were activated in vitro and infected with Bcl-XL or control retroviruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 23 publications
5
45
0
Order By: Relevance
“…Okkenhaug et al recently reported that distinct sequences in the intracellular portion of CD28 are responsible for the proliferative and for the anti-apoptotic functions of CD28-mediated costimulation [29]. Similarly, Dahl et al reported that constitutive expression of the anti-apoptotic molecule Bcl-x L was not able to compensate for the lack of costimulation [30], again suggesting that the proliferative and anti-apoptotic effects of CD28 are mediated independently.…”
Section: Discussionmentioning
confidence: 95%
“…Okkenhaug et al recently reported that distinct sequences in the intracellular portion of CD28 are responsible for the proliferative and for the anti-apoptotic functions of CD28-mediated costimulation [29]. Similarly, Dahl et al reported that constitutive expression of the anti-apoptotic molecule Bcl-x L was not able to compensate for the lack of costimulation [30], again suggesting that the proliferative and anti-apoptotic effects of CD28 are mediated independently.…”
Section: Discussionmentioning
confidence: 95%
“…CD28:B7 signaling is the best characterized and an important costimulatory pathway for naive T cell activation, including cytokine production, clonal expansion, and prevention of anergy and T cell survival (34,35). However, blocking CD28:B7 pathway wasn't effective in inducing tolerance to murine skin and islet transplantation (36,37).…”
Section: For a Review)mentioning
confidence: 99%
“…In a double-blind, placebocontrolled, cross-over study [54] tremor was improved by theophylline (dose: 150 mg/day) in 80 % of patients (compared with 60 % of the propranolol-treated arm). One placebocontrolled small study has shown an effect of gabapentin (1800 mg and 3600 mg) [55], while another failed [56], and 1 small crossover study with propranolol has shown similar improvement for both drugs [57].…”
Section: Possibly Efficacious Drugsmentioning
confidence: 99%